Peran Penyuntingan Bahasa dalam Meningkatkan Pemahaman Bahasa Siswa - Liza Handayani Batu Bara (Lentera Jurnal, 2025)
The role of language editing in students’ language comprehension is increasingly important, with reading and writing as the main activities in language learning. Effective language editing can significantly improve students' understanding of language and their language skills. This comprehensive study aims to enhance students’ language comprehension through the role and implications of language editing. The research uses qualitative library research, with books and journal articles as data sources, and a documentation approach, which is analysed with descriptive or analytical data analysis techniques. The study's results, derived from a comprehensive research process, show that language editing's role in students’ language comprehension includes aiding students in grammar, expanding vocabulary, understanding the link between vocabulary and meaning, and improving communication.